A metodologia de resolução de problemas e o aplicativo Winplot para a construção do conceito de função por alunos do ensino médio - Santos, Noélli Ferreira dos (2013)
This paper aims to analyze the contributions of the Methodology Problem Resolutions coupled with Winplot application to build the concept of function by high school students. The participants were students of the 1st year of High School of the Escola Estadual Padre Rômulo Zanchi in the city of Santa Maria. The research was a qualitative, grounded in cultural-historical theory of Vygotsky and Methodology Problem Resolutions. The instruments used involved two questionnaires, observations of activities, a daily classroom, as well as the documentary record of the students in the use of application Winplot. The questionnaires showed that the students use the computer for leisure and expressed interest in using it for learning math. As for your previous knowledge, the students have difficulties on content function. After the activities are applied, the results analysis, it was found that students were able to analyze the numerical data, understand the variations of the quantities involved, algebraic and graphical form relationships more accurately, and can interpret and observe changes performed on each chart and other information and properties, allowing the appropriation of the concept of function and could be a basis for the understanding of other mathematical functions. However there were some difficulties faced by students, especially with regard to reading and interpreting graphs. The most significant is that students engaged with the technological resources and motivated with more diverse classes, where students exchange information and learning. The computerized environment and methodology required participation and discussion by changing the traditional setting of the classroom. So the teacher had to be open to pedagogic as well as technological innovations, thus providing a more dynamic and innovative learning.